Synthesis of Hydrophobic Filler for Polymer Composites - I. Pavlenko, V; I. Cherkashina, N (International Journal of Engineering and Technology, 2018)
Silica (SiO2) particles are increasingly more used for the productions of polymer composites. But introduction of silica in polymer disturbs the natural structure uniformity also this technique is difficult with the aid of the high propensity of silica to agglomeration. So to create polymer composites it is better to use fillers with a hydrophobic surface. In this study, it was investigated the possibility of surface amendment of Silica particles for their hydrophobization. Silica particles had been organized by way of the tetraethyl orthosilicate hydrolysis reaction at high temperature and pressure. The morphology and shape of the silica were studied by way of X-ray powder diffraction, approach of particle measurement analysis by using laser diffraction, and electron micrograph. For floor amendment of silica particles was use hydroalcoholic answer of sodium methylsiliconate. The bought results of the contact perspective measurements show that the floor of initial particles of silica is hydrophilic (contact perspective – 74°). The surface of Silica particles after the change are strongly hydrophobic (contact angle – 92-126°). The most suitable is the introduction of a modifier in an amount of 2%..